Proactive and reactive control by the medial frontal cortex - Stuphorn, Veit; Emeric, Erik (Frontiers in Neuroengineering, 2012)
Adaptive behavior requires the ability to flexibly control actions. This can occur either proactively to anticipate task requirements, or reactively in response to sudden changes. In this article, we describe the behavioral and physiological evidence for dual mechanisms of control in response inhibition in the medial frontal cortex in the context of the stop signal or countermanding task.